2013
DOI: 10.1165/rcmb.2013-0040oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inflammatory Cytokines TNF-α and IL-13 on Stromal Interaction Molecule–1 Aggregation in Human Airway Smooth Muscle Intracellular Ca2+ Regulation

Abstract: (20,21). STIM1 has been demonstrated to constitute a transmembrane protein predominantly localized in the SR membrane (22). The luminal N-terminal region of STIM1 contains an EF-hand domain and a sterile a motif (SAM) domain. Beyond a transmembrane region, STIM1 also contains a long cytoplasmic C-terminal domain, which is proposed to be the site of interactions with Orai1 to trigger SOCE (23). STIM1 senses the depletion of SR Ca 21 through its low-affinity Ca 21 -binding EF-hand domain. Upon sensing SR Ca 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Accordingly, the limited but interesting data that asthmatic ASM cells have a higher amplitude of [Ca 21 ] i responses to AA raise the question of whether ARC channels are potentially contributory to increased [Ca 21 ] i in asthmatic ASM. Although the mechanisms for such up-regulation were beyond the scope of this study, enhanced Orai3 expression (or activation) may be involved, and would be consistent with previous findings that related mechanisms, such as STIM1, Orai1, and even caveolin-1, are upregulated in human ASM after inflammation (11,24,25). Furthermore, inflammation can result in enhanced expression of SR Ca 21 proteins and functionality, and AA-induced influx could produce greater SR Ca 21 responses, leading to greater contraction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Accordingly, the limited but interesting data that asthmatic ASM cells have a higher amplitude of [Ca 21 ] i responses to AA raise the question of whether ARC channels are potentially contributory to increased [Ca 21 ] i in asthmatic ASM. Although the mechanisms for such up-regulation were beyond the scope of this study, enhanced Orai3 expression (or activation) may be involved, and would be consistent with previous findings that related mechanisms, such as STIM1, Orai1, and even caveolin-1, are upregulated in human ASM after inflammation (11,24,25). Furthermore, inflammation can result in enhanced expression of SR Ca 21 proteins and functionality, and AA-induced influx could produce greater SR Ca 21 responses, leading to greater contraction.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, capacitative Ca 21 entry in response to intracellular store depletion (i.e., SOCE) is an important mechanism in ASM (9)(10)(11)25). However, there is increasing evidence in nonexcitable cells for an additional noncapacitative Ca 21 influx mechanism regulated by AA (13,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PC12 cells, changes in extracellular pH can influence store-operated Ca 2ϩ influx that is dependent on the SR Ca 2ϩ protein stromal interacting molecule 1 (STIM1) (299). Given the important role of STIM1/Orai1 in human ASM (80,137,225,264,292,357), it is possible that OGR1 could modulate store-operated Ca 2ϩ entry (SOCE) by enhancing STIM1 interactions with Orai1 or other channels that contribute to Ca 2ϩ influx, particularly canonical transient receptor potentials (TRPCs) (80,338). Furthermore, the limited data in human ASM suggest that OGR1 can further result in p42/44 MAPK phosphorylation (269) and IL-6 production (122) and therefore have more complex effects in the setting of disease.…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…They reported that rat airway SMC proliferation in response to serum and TGF␤1 was partly reduced by 10 M SKF-96365 (27). Jia et al (37) showed that IL-13 and TNF␣ enhance puncta formation of ectopically expressed fluorescently tagged STIM1 and increased SOCE in airway SMCs, suggesting that inflammatory cytokines might contribute to airway hyperresponsiveness through increased SOCE in human airway SMCs during disease.…”
Section: Soce In Smooth Musclementioning
confidence: 99%